Comparison of exhaled nitric oxide levels in pediatric patients with allergic rhinitis. (November 2019) - Sapsaprang, Siwaporn; Tanticharoenwiwat, Pattara; Kulalert, Prapasri; Poachanukoon, Orapan; Setabutr, Dhave
Abstract: Objective: To determine whether the measurement of exhaled nitric oxide (eNO) can help distinguish children with allergic rhinitis (AR) from healthy controls and whether eNO in children with AR correlates with disease severity. Methods: From August 2015 to 2016, children aged 5–15 years of age grouped into those with allergic rhinitis (n = 40) and those classified as healthy control subjects (n = 40) had exhaled nitric oxide (eNO) levels measured. The eNO level was additionally compared to the patient's clinical disease severity according to the ARIA (Allergic Rhinitis and its Impact on Asthma) classification. Results: Mean eNO in children with AR (12.64 ± 14.67 ppb) was significantly higher than that in the healthy control group (7.00 ± 6.33 ppb) ( p-value = 0.046 ). In the persistent AR group (17.11 ± 18.40 ppb), eNO level was significantly higher than individuals in the intermittent AR group (8.59 ± 8.88 ppb, p-value = 0.024) and the healthy control group (7.00 ± 6.33 ppb, p-value = 0.008 ). Among children with AR, eNo was not significantly different with relationship to gender, age, weight and passive smoking exposure. Conclusions: Exhaled nitric oxide may be elevated in children with AR that do not have concomitant asthma. This suggests exhaled nitric oxide may show utility as a parameter to monitor the severity of allergic rhinitis and to monitor the efficacy of the treatment. Physicians should consider comorbid AR when utilizing exhaled nitric oxide as a monitoring parameter in the treatment of asthma.